Prevalência da síndrome metabólica em gestantes - Heinzen, Marian Gizele Lorenzetti (2019)
The Metabolic Syndrome (MS) is characterized by a set of disorders of metabolic origin, such as hypertension, dyslipidemia and diabetes, which, when present during the gestational period can lead to several health problems not only for the pregnant woman but also for the fetus or newborn (RN). In addition, MS can be a risk factor for developing of cardiovascular disease (CVD) and the persistence of diabetes even after pregnancy. In this context, the aim of this study was to determine the prevalence of metabolic syndrome in pregnant women served by the Unified Health System (SUS) in the city of Francisco Beltrão – PR. For this, 141 pregnant women from the public health system were evaluated for parameters of MS, such as total cholesterol and fractions, triglycerides and glycemia. Basal insulin levels were measured and used to calculate the HOMA-IR insulin resistance index. Blood pressure (BP) was measured at the time of blood collection. Measurements of height and weight pre-pregnancy for the calculation of body mass index (BMI) were collected from secondary sources (pregnant’s woman follow-up card). MS was defined according to National Cholesterol Education Program / Adult Treatment Panel III (NCEP / ATP III) criteria, with adaptations proposed by Chatzi et al. (2009). Five diagnostic criteria were evaluated, among which, for the classification of MS, it was necessary to have 3 or more criteria, which were identified in 19 pregnant women. Therefore, the prevalence of MS was 13.4%. Among these, 10.5% had altered fasting glycemia, 78.9% had a BMI greater than 30 kg/m2 prior to gestation, 89.4% had an increased triglyceride level, 94.7% had low HDL cholesterol levels, and 36.8% had elevated blood pressure. Of the 141 pregnant women who were part of the sample, 35 (24.8%) presented two of the five diagnostic criteria. The total prevalence of altered fasting glycemia was 10.5%, BMI greater than 30 kg/m2 was 16.3%, triglyceride level above 150 mg/dL was identified in 63.5% of pregnant women, 44.6% had lower HDL levels to 50 mg/dL and hypertension was identified in 6.3% of the sample. Moreover, in pregnant women was identified with MS insulin resistance and insulin levels are shown as independent factor for overweight, which was strongly associated with MS. Thus, through this work, it was possible to demonstrate the prevalence of MS in the pregnant women of Francisco Beltrão and also to identify the presence of risk factors for metabolic and cardiovascular complications that could lead to negative outcomes for the pregnant woman and the fetus.